Analysis of Improving Employee Performance at the BTN Sharia Semarang Branch through Career Adaptability and Work Engagement - Ariansyah, Dikka Galih; Widayati, Tri (Faculty of Economics and Business UNTAG Semarang, 2023)
The roles of career adaptability and work engagement are very important for the performance of banking employees so that companies can compete. This study aimed to analyze the factors of increasing employee performance at the Bank Tabungan Negara (BTN) Sharia Semarang Branch through career adaptability and work engagement. This study uses an explanatory analysis approach. Census was used to obtain 70 employees as samples. Multiple regression was used to examine the role of these factors. The results found that career adaptability and work engagement variables can explain employee performance variables of 72.9%. Career adaptability and work engagement are proven to have a positive and significant effect on employee performance. It is hoped that the Management of BTN Sharia Semarang Branch will continue to improve the career adaptability and work engagement of employees by continuing to provide enthusiasm, enthusiasm, and trying seriously to be able to improve employee performance.